Venous catheterization. Clinical investigation of your problems and complications - Cid, A.; Verderosa, W; Rodrigo, C.; Arismendi, A.; Rey, N; Medina, N (Cirugía del Uruguay, 1973)
Clínica! research on central venous catheterization and ensuing complications, the reasons for this research, its goals, the material and methods employed, are described by the authors. Results obtained are analyzed and discussed. Special stress is laid on the importance of radiological control, due to the frequency ( 30 % ) with which the catheter takes an anomalous position. 'I'he paper includes the conclusions arrived at.